Torsional osteotomies of the femur. Issue 3 (17th November 2014) - Dickschas, Jörg; Harrer, Jörg; Reuter, Benoit; Schwitulla, Judith; Strecker, Wolf
Abstract Various pathologies of the hip or knee, such as patellofemoral malalignment or femoroacetabular impingement may be caused by a femoral torsional deformity. When diagnosed and analyzed, it is treated by femoral torsional osteotomy. Thirty femoral torsional osteotomies in 25 patients were included, the principal symptoms were patellar dislocation in 15 patients, anterior knee pain in 17, and femoroacetabular impingement in two. A computed‐tomography‐based measurement of the torsional angle was performed in all patients. Japanese Knee Society score, Tegner activity score, Lysholm score, and visual analog scale score were determined before surgery and at follow‐up after 41 (6–113) months. Femoral internal torsion was on average 40.9° (29° − 66°; normal 24°). Surgical treatment consisted of a femoral external torsional osteotomy of on average 13.8° (5° − 26°). Tegner activity score increased non‐significantly (p‐value 0.326) from 3.57 to 3.71. Japanese Knee Society score improved significantly from 72 to 87 (p‐value 0.004) while Lysholm score rose significantly from 66 to 84 points (p‐value 0.004). Pain relief was demonstrated by a significant decrease in the VAS score from 5.6 to 2.4 (p‐value 0.007). No further patellar dislocation was reported. Torsional deformities of the femur frequently cause symptoms in the knee or hip joint. After thorough assessment and diagnostic investigation, a femoral external torsional osteotomy provides significant pain relief as well as patellofemoral stability. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???–???, 2015.